Experimental demonstration of enhanced solar energy utilization in flat PV (photovoltaic) modules cooled by heat spreaders in conjunction with cotton wick structures. (October 2015) - Chandrasekar, M.; Senthilkumar, T.
Abstract: A passive thermal regulation technique with heat spreaders in conjunction with cotton wicks is developed for controlling the temperature of PV module during its operation. Experiments were conducted with the developed technique in the location of Tiruchirappalli (78.6°E & 10.8°N), Tamil Nadu, India with flat 25 Wp PV module and its viability was confirmed. The thermal and electrical performances of thermally regulated flat PV module were also compared with the results of flat PV module without cooling system. The PV module temperature was reduced by 12% while the electrical yield is increased by 14% with the help of the developed cooling system. Basic energy balance equation applicable for PV module was used to evaluate the thermal loss coefficient which was found to increase due to fin effect of heat spreader and evaporative cooling in moist cotton wicks. Highlights: Passive cooling system for flat PV with heat spreader and cotton wick structures is proposed. Temperature is controlled due to evaporative cooling and fin effect. PV module temperature is reduced by 12% with the proposed cooling system. PV electrical yield is increased by 14% with the proposed cooling system.